Anatomical variations of mandibular canal using cone-beam computed tomography - A retrospective study - Satarupa Chanda; Reema Manoj; Easwaran Ramaswami; Vasavi Santosh; Mandavi Waghmare; Sonal Vahanwala (Wolters Kluwer Medknow Publications, 2021)
Background: Precise anatomy and course of mandibular canal is important to obtain the desired outcome of different mandibular surgical procedures and circumvent various surgical complications. This study aimed to document the presence, frequency, and type of mandibular canal variations using cone-beam computed tomography (CBCT). Materials and Methods: CBCT images of 100 patients with a total of 200 sides (right and left) were obtained retrospectively from the database of Government Dental College and Hospital, Mumbai. The presence and type of mandibular canal variation were evaluated and classified according to Naitoh et al. classification (2009) along with Rashsuren et al. modification (2014). Prevalence rates were determined according to gender, side of the mandible, and type. Morphometric analysis of the mandibular canal variations was made. Statistical analysis with Chi-square, analysis of variance (ANOVA), and Scheffe's tests were performed. Results: Mandibular canal variations were found in 13% of patients and 8% of total sides. Type I dental canal (37.50%) was the most common type of accessory canal followed by Type II retromolar canal (31.25%), Type III forward canal type (25%), Type V trifid canal (6.25%), and Type IV buccolingual canal (0%). The retromolar canal had the maximum length and diameter and most of the accessory mandibular canals (60%) had a diameter of more than 50% of that of the main canal. Conclusion: Bifid mandibular canal was the most common anatomical variation of the mandibular canal found in this study with dental canal type being the most frequent type. To avoid iatrogenic injuries, a presurgical detailed evaluation of the mandibular canal using CBCT was suggested.